2013
DOI: 10.4103/0973-029x.125230
|View full text |Cite
|
Sign up to set email alerts
|

Orthokeratinizing odontogenic cyst of maxilla with complex odontoma

Abstract: The orthokeratinized odontogenic cyst (OOC) and odontoma are the odontogenic cyst and tumor respectively that are minimally invasive neoplasms of head and neck region. OOC is a rare variant of odontogenic cyst characterized by the presence of excessive orthokeratin covering the cystic lining. Odontoma is a benign neoplasm/hamartoma often discovered accidently on panoramic radiographs. We came across a case of a 26-year-old male with swelling on his face along with difficulty in breathing. On the basis of radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It presents as solitary, unilocular radiolucency in the posterior mandible with cortical expansion. [ 2 3 4 ] In contrast, the present case is unique as it occurred in an 18-year-old female patient and showed calcification. Only one case has been reported till date with calcification.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…It presents as solitary, unilocular radiolucency in the posterior mandible with cortical expansion. [ 2 3 4 ] In contrast, the present case is unique as it occurred in an 18-year-old female patient and showed calcification. Only one case has been reported till date with calcification.…”
Section: Introductionmentioning
confidence: 53%
“…[ 5 ] The recurrence rate OOC is 2.2% which is far low than that of KCOT (recurrence rate 42.6%). [ 3 15 ] Table 1 summarizes the differences between OOC and OKC.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators believe that OKC is a neoplasm, which they prefer to call a keratocystic odontogenic tumor (KCOT) (9). According to the WHO classification, oral cystic lesions lined by orthokeratinized epithelium are not included in the spectrum of KCOT, as the lining epithelium of OOC lacks the typical features of OKC and has lower proliferative activity (10). It has been suggested that KCOT may arise from the dental lamina, but OOC may arise from the oral epithelium under the influence of the dental papilla or only the oral epithelium (11), and for OOCs associated with an impacted tooth, a different histogenesis has been suggested (12).…”
Section: Discussionmentioning
confidence: 99%